Bibliometric Study of Scientific Production on Educational Inspection - Antonio José Moreno Guerrero (Universidad Autónoma de Madrid, 2019)
The educational inspection, as part of administrative of the educational inspection, preserves and defends the quality of the education, being a reference for the improvement of the same. The methodology of applied research is a bibliometric analysis through the markers "Inspection in Education", "Educational Inspection", "School Inspection", "Inspection of Education", "Educational Supervision", with a total of 92 documents analyzed. The main author gender, number of authors, year of publication, institution authors, first surname authors, keywords, type of document, name of the journal, research methodology, study population, research instruments, other works have been taken into account cited, number of references in the article, research conclusions and impact factor. It is observed that the scientific texts focused on the educational inspection are of an authorship, made by men, applying a qualitative methodology, through the analysis of documents, with references inferior to 20 documents, being the year 2017 the biggest year of production, with articles indexed in Latindex and creations of scientific texts by the inspection of Andalusia, whose most used words are "Education" and "Inspection".